2000
DOI: 10.1111/j.1528-1157.2000.tb00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Seizure Outcome in 74 Patients with Lennox–Gastaut Syndrome: Effects of Incorporating MRI Head Imaging in Defining the Cryptogenic Subgroup

Abstract: Summary:Purpose: To determine if using more stringent criteria for cryptogenic Lennox-Gastaut syndrome (LGS) would result in an improved prognosis for that group. Cryptogenic, symptomatic, and non-cryptogenic LGS patients without etiology (indeterminate) were compared with respect to seizure and cognitive outcome.Methods: Retrospective chart review was performed on 245 patients seen at the Mayo Clinic Rochester from 1976 to 1997, with a diagnosis of either LGS or slow spike wave on EEG.LGS was confirmed in 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
14

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 8 publications
(5 reference statements)
6
81
0
14
Order By: Relevance
“…At follow-up of at least 10 years, 5-13% of individuals were in remission and 8% were not mentally retarded. Patients with cryptogenic LGS had a better cognitive outcome compared with patients who had symptomatic LGS [38], but another study reported no difference between the groups [39]. …”
Section: Catastrophic Epilepsies Of Childhoodmentioning
confidence: 97%
See 1 more Smart Citation
“…At follow-up of at least 10 years, 5-13% of individuals were in remission and 8% were not mentally retarded. Patients with cryptogenic LGS had a better cognitive outcome compared with patients who had symptomatic LGS [38], but another study reported no difference between the groups [39]. …”
Section: Catastrophic Epilepsies Of Childhoodmentioning
confidence: 97%
“…LGS is often (in 13-65% of cases), and in cases of symptomatic etiology in particular, a continuation of West syndrome [36,38,39]. However, as shown in a communitybased study, prenatal or perinatal abnormalities are not necessarily in correlation with the severity of epilepsy [40].…”
Section: Catastrophic Epilepsies Of Childhoodmentioning
confidence: 99%
“…The use of corticosteroids has also been described in LKS, Ohtahara syndrome and in LGS, particularly for the treatment of periods of nonconvulsive status epilepticus. Only a minority of patients with EE achieve seizure freedom [126,127]. The main goal of pharmacotherapy is a reduction in the frequency and severity of seizures to improve quality of life [28].…”
Section: Hormonal Treatmentsmentioning
confidence: 99%
“…2 The majority of patients with symptomatic LGS experience more than 3 seizures per day. 3 The seizure types that are most frequently observed in LGS are tonic, atypical absence, atonic, myoclonic, generalized tonic-clonic, and focal onset (previously referred to as partial onset) seizures. [3][4][5] Patients with LGS experience frequent seizures, usually during sleep, with 10-20 Hz fast rhythms.…”
Section: Introduction: Lennox-gastaut Syndromementioning
confidence: 99%
“…2 The median age of LGS onset is ~4 years. 3 Many patients (46.9%, by one estimate) who develop LGS during childhood continue to present the complete disease profile into adulthood. 10 For the majority of patients with LGS, seizures remain difficult to treat, [11][12][13] and most of the patients cannot live independently as adults.…”
Section: Introduction: Lennox-gastaut Syndromementioning
confidence: 99%